Adaptive algorithms for researching problems in a variable computer environment: Fìz.-mat. model. ìnf. tehnol. 2021, 33:181-185 - Khimich, Alexander; Chistyakova, Tamara; Sydoruk, Volodymyr; Yershov, Pavel (PHYSICO-MATHEMATICAL MODELLING AND INFORMATIONAL TECHNOLOGIES, 2021)
The paper considers tools for studying computer models of problems in modeling physical and technical processes. Adaptive algorithms for studying structural and mathematical properties and solving problems in a variable computer environment are presented. The proposed innovative functionality is integrated into the intelligent computer mathematics system. References Goldreich, O. (2001). Foundations of Cryptography. Volume 1. Basic Tools. – London: Cambridge University Press. Retrived from www.top500.org Khimich, A. N., Molchanov, I. N., Popov, A. V., Chistyakova, T. V., Yakovlev, M. F. (2008). Parallel Algorithms for solving problems of computational mathematics. Kiev: Nauk. Dumka publ. (in Russian). Khimich, A. N., Molchanov, I. N., Mov,a V. I. (2007). Numerous software for the mimd computer Inparkom. Kiev: Nauk. Dumka. (in Russian). Khimich, A., Sydoruk, V., Yershov, P. (2019). "Intellectualization Of Computation Based On Neural Networks For Mathematical Modeling," 2019 IEEE International Conference on Advanced Trends in Information Theory (ATIT), Kyiv, Ukraine. doi: 10.1109/ATIT49449.2019.9030444. DOI https://doi.org/10.1109/atit49449.2019.9030444 Khimich, A. N., Sidoruk, V. A. (2019). Use of mixed bit depth in mathematical modeling. Mathematical and computer modeling. Series: physical and Mathematical Sciences. Sat. scientific works, 19, 180-187. (in Ukrainian). DOI https://doi.org/10.32626/2308-5878.2019-19.180-187